Prognostic value of blood glucose trajectories in critically ill patients with intracerebral hemorrhage: A retrospective cohort study - Huan Zuo; Xin Zuo; Yaxin Zhang; Weihong Zheng (PLoS ONE, 2026)
Background Abnormal glucose regulation is common in critically ill patients with intracerebral hemorrhage (ICH), but the prognostic relevance of early glucose patterns remains unclear. We aimed to identify early blood glucose trajectories in ICU patients with ICH and evaluate their association with short-term mortality. Methods Adult patients with ICH were identified from the MIMIC-IV database. Latent class analysis was applied to blood glucose measurements obtained within the first 36 hours after ICU admission to identify distinct glucose trajectory classes. Cox proportional hazards models were used to assess the association between glucose trajectories and 28-day in-hospital mortality with multivariable adjustment. A 36-hour landmark analysis and sensitivity analyses including patients with ICU length of stay <36 hours were conducted to evaluate robustness. Results A total of 1,978 patients were classified into three glucose trajectory classes: stable normoglycemia, a U-shaped pattern with initial severe hyperglycemia, and an inverted U-shaped pattern with marked glycemic fluctuation. Compared with the stable group, both unfavorable trajectory classes were associated with significantly higher 28-day in-hospital mortality after full adjustment ( P <  0.05). These associations were consistent across landmark and sensitivity analyses. Kaplan–Meier analyses demonstrated significant survival differences among trajectory classes, and subgroup analyses suggested effect modification by age and diabetes status. Conclusions Early blood glucose trajectories within the first 36 hours after ICU admission are independently associated with 28-day in-hospital mortality in patients with ICH. Dynamic glucose patterns may provide additional prognostic value for early risk stratification.